2021
DOI: 10.3390/app11209363
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Dental Protection and the Material Arrangement in Custom-Made Mouthguards

Abstract: Experimental research studies have shown that wearing a mouthguard (MG) is an effective way to prevent tooth or maxillofacial trauma. However, there is a lack of scientific information regarding how the material arrangement within the mouthguard can modify its mechanical response during an impact. Hence, this study aimed to evaluate the influence of material arrangement within custom-made mouthguards on stress transmitted to anterior teeth, bone, and soft tissue after impact. Four 3D finite element models of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Similarly, another finite element study indicated the effectiveness of using the rigid occlusal splint to change the distribution of functional load in the treatment of patients with mastication muscle parafunction [ 35 ]. This study corroborates both of these studies in presenting a positive effect to reduce the jaw displacement and teeth stress with use of the hybrid mouthguard (HMG), therefore potentially reducing the trauma effects [ 36 , 37 , 38 ] and the management of injured patients [ 37 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, another finite element study indicated the effectiveness of using the rigid occlusal splint to change the distribution of functional load in the treatment of patients with mastication muscle parafunction [ 35 ]. This study corroborates both of these studies in presenting a positive effect to reduce the jaw displacement and teeth stress with use of the hybrid mouthguard (HMG), therefore potentially reducing the trauma effects [ 36 , 37 , 38 ] and the management of injured patients [ 37 ].…”
Section: Discussionsupporting
confidence: 79%
“…The simulated force was applied in just one direction. However, forces may be applied from other regions that could generate different results [ 3 , 4 , 35 , 38 ]. In addition, the elastic modulus was isotropic, which is different than human tissue [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61] EVA material variations have included silver nanoparticles to add antibacterial properties, 62 and additions to enhance shock absorbance have included porous rubber, silicone interlayers, 63 silicon nylon mesh, 64,65 and urethane modifications. 66 Additional performance-enhancing adaptations have included internal air cells either alone, 67,68 or combined with hard material inserts, 69 closed cell foam, 67 A-silicone interlayers, 70 and "honeycomb" internal EVA mesh. 68 Other materials considered and used include controlled microstructure polystyrenepolyolefin copolymer-based materials that are proposed to provide enhanced performance compared to EVA, 61,71 increased flexibility afforded by thermosetting ternary novel thiolene "click" polymer systems, modified with urethane as well as acrylate, 55,56 and polyolefin copolymer-based materials that offer lower water absorption and higher impact resistance than EVA.…”
Section: Sm Materialsmentioning
confidence: 99%
“…Stress absorption assessments have included strain gauge sensors, 18 Fiber Bragg grating strain sensors, 18 film sensors, 83 laser triangulation sensors, 65 laser Doppler vibrometers, 84 solid‐state NMR pulse measurements, 53 and 3D image correlation strain analysis 85 . While largely underutilized, finite element analysis (FEA) of SM function has been described that allows the in silico computational, non‐destructive virtual analysis of complex structures that would be difficult to derive using in vitro methods 9,10,18,59,68,75,86 . Both 2D FEA that can perform planar stress and strain analysis has been reported, 9 as well as 3D FEA that can evaluate biomechanical responses and stress dissipation over wider areas 10,59,68,75,86 .…”
Section: Introductionmentioning
confidence: 99%